PROFIL DISOLUSI TABLET LEPAS LAMBAT KALIUM DIKLOFENAK MENGGUNAKAN PATI PREGELATINASI TALAS PRATAMA (Colocasia esculenta (L). Schott var. Pratama) - Desy Nawangsari; Rani Prabandari; Ammanu Kurniadi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Starch is one of the commonly used excipients in tablet preparations. Natural starch has limitations in the form of poor flow rate and compressibility, so it is not suitable for use in the manufacture of tablets by direct compression. One source of plants that produce starch and has not been widely developed is (Colocasia esculenta (L). Schott var. Pratama). The purpose of this study was to modify (Colocasia esculenta (L). Schott var. Pratama) starch by gelatinization used in diclofenac potassium slow-release tablets. This research is a type of laboratory experimental research that begins with the isolation of starch from taro tubers, modification of starch by pregelatinization, manufacture of diclofenac potassium slow release tablet press mass, evaluation of physical properties and finished tablet dissolution tests. The results of the printing mass test showed that the use of (Colocasia esculenta (L). Schott var. Pratama) pregelatinated starch matrix had good flowability. The results of the tablet test showed that the average tablet weight was 209 ± 3.40 mg, the diameter and thickness were 7.69 ± 0.02 and 2.82 ± 0.01 mm respectively, the hardness was 7.00 ± 0.35 kg, the friability was 0. 73 ± 0.27 % and disintegration time 65.33 ± 2.52 minutes and the dissolution results showed that within 8 hours the potassium diclofenac sustained release tablet dissolved 60.20%. Based on the physical properties and dissolution tests performed, it can be concluded that the use of pregelatinated modified starch as a matrix in diclofenac potassium slow-release tablets fulfills the specified test parameters.